The representation and practice of interdisciplinarity in health policy and systems research : a systematic review - MacQuilkan, Kim Elizabeth (Health Policy and Systems Division, 2016)
The emerging field of Health Policy and Systems Research (HPSR) developed from a variety of disciplines, orientated around the common research agenda of strengthening health systems, which are understood to be both complex and dynamic. The diversity of contributing disciplinary influences is a core feature of HPSR and hence the field is clearly defined as 'interdisciplinary'. However there has been a paucity of research conducted on interdisciplinarity within HPSR, with a lack of clarity on its conceptualization and practice. This study explores the representation of interdisciplinarity, and interdisciplinary practices within HPSR, utilising scoping and systematic review approaches. It is revealed that the term 'interdisciplinarity' (and its variations) have suffered from misuse and confusion. In particular, there is limited practice of an 'integrationist' interdisciplinary perspective and practice within HPSR - despite key HPSR authors supporting the integrationist approach due to its alignment with the HPSR scope of study to address complex health system problems. Over the last ten years, there has been a significantly increased output referenced as part of the HPSR field, however there is a scarcity of interdisciplinary research examples that have intentionally integrated multiple disciplinary influences. This research shows that current HPSR literature mainly reflects a 'generalist' interdisciplinary perspective (which only requires the presence of multiple disciplinary influences) rather than the integrationist perspective (which require intentional integration of influences). As a result, we propose improved approaches to framing, funding, and teaching interdisciplinary HPSR.